2015
DOI: 10.1007/s11999-014-3980-4
|View full text |Cite
|
Sign up to set email alerts
|

What Factors Predict Improvements in Outcomes Scores and Reoperations After the Bernese Periacetabular Osteotomy?

Abstract: Background The Bernese periacetabular osteotomy (PAO) has entered its fourth decade and is frequently used for corrective osteotomy in patients with acetabular dysplasia. Although our capacity to preserve the joint after corrective osteotomy is excellent, gaining a better understanding on how well patients function after this surgery is important as well. Questions/purposes (1) What changes in patient-reported outcomes scores occur in patients treated with PAO for hip dysplasia in the setting of a single-surge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
39
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 59 publications
(44 citation statements)
references
References 25 publications
5
39
0
Order By: Relevance
“…In our study, the mean long-term postoperative UCLA Activity Score was 7 ± 2 for the asymptomatic hips and 6 ± 2 for symptomatic hips. These results are comparable to Beaulé et al's [5] and van Bergayk and Garbuz' [44]. We are able to show at long-term followup that patients undergoing PAO whether asymptomatic or symptomatic are able to remain regularly active.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…In our study, the mean long-term postoperative UCLA Activity Score was 7 ± 2 for the asymptomatic hips and 6 ± 2 for symptomatic hips. These results are comparable to Beaulé et al's [5] and van Bergayk and Garbuz' [44]. We are able to show at long-term followup that patients undergoing PAO whether asymptomatic or symptomatic are able to remain regularly active.…”
Section: Discussionsupporting
confidence: 89%
“…Few studies have reported on activity-related and quality-of-life outcomes after PAO. Beaulé et al [5] in their 2014 series on dysplastic hips reported a preoperative UCLA score of 5.3 with an improvement to 6.6 at a median of 5 years postoperative followup. van Bergayk and Garbuz [44] reported on quality of life and sports-specific outcome measures on a small cohort of 22 patients with followup of 2 years.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The risk of total hip arthroplasty at five years after periacetabular osteotomy was 12% in hips with a preoperative Tönnis grade of 0 or 1 and 27% in hips with a Tönnis grade of 2. In a more recent study of the predictors of clinical outcome after periacetabular osteotomy, Beaulé et al 94 found that a higher preoperative alpha angle was significantly associated with a lower functional score postoperatively, potentially indicating more severe articular damage persisting after surgical correction. Anteroposterior pelvic radiograph after a periacetabular osteotomy was done on the right hip with correction of acetabular retroversion.…”
mentioning
confidence: 99%